THE EXISTENCE OF HOUSEWIVES IN THE INSTAGRAM - Sjoraida, Diah Fatma; Anwar, Rully Khairul; Rizal, Edwin; Rejeki, Diah Sri (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: Social media and housewives have become an inseparable unity, especially in Karawang. Accessing social media is a routine that is always done every day. Existence or self-actualization is the reason housewives have social media accounts, one of the Instagram. The purpose of this study is to determine the motives of housewives have Instagram and to know the forms of interaction and content that are distributed to the public.Purpose: This study aims to determine the impact of the use of Instagram on consumptive behavior of housewives in Karawang.Method: This qualitative research uses a descriptive method by taking a location on a housewife in Karawang.Findings: The motive of housewives using Instagram is quite religious, that is entertainment, selling its business, product, socialization, and self-existence, the form of interaction and content distributed in Instagram is post photo with caption interesting, giving hashtag, and follow the trends in Instagram. The conclusion of this research is through Instagram, the housewife can show their existence to the environment to be seen and accepted well.Conclusion: 1) Instagram is a phenomenal social media among housewives because users are spoiled with various features available on Instagram, 2) the campus provides a large bandwidth so they can access Instagram more easily, and 3) the impact of expanding access to the internet becomes they are more consumptive to do transactions face to face.